2001
DOI: 10.1021/bi010656k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Basis for Suicide Inactivation of Porphobilinogen Synthase by 4,7-Dioxosebacic Acid, an Inhibitor That Shows Dramatic Species Selectivity

Abstract: 4,7-Dioxosebacic acid (4,7-DOSA) is an active site-directed irreversible inhibitor of porphobilinogen synthase (PBGS). PBGS catalyzes the first common step in the biosynthesis of the tetrapyrrole cofactors such as heme, vitamin B 12 , and chlorophyll. 4,7-DOSA was designed as an analogue of a proposed reaction intermediate in the physiological PBGS-catalyzed condensation of two molecules of 5-aminolevulinic acid. As shown here, 4,7-DOSA exhibits time-dependent and dramatic species-specific inhibition of PBGS e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 34 publications
(79 reference statements)
5
68
0
Order By: Relevance
“…PBGS proteins that require the allosteric magnesium, the magnesium binding site is located at the arm-to-barrel interface of the hugging dimer. This binding site is absent in the hexamer (1,3,14,15). Previously reported data showed that addition of magnesium favors the largest form (octameric) during native gel electrophoresis (14).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…PBGS proteins that require the allosteric magnesium, the magnesium binding site is located at the arm-to-barrel interface of the hugging dimer. This binding site is absent in the hexamer (1,3,14,15). Previously reported data showed that addition of magnesium favors the largest form (octameric) during native gel electrophoresis (14).…”
Section: Discussionmentioning
confidence: 91%
“…Succinyl acetone is also a commonly used inactivator of PBGS and has physiologic significance in the inactivation of human PBGS for patients with hereditary tyrosinemia (10, 11). 4,7-DOSA and succinyl acetone (10) are active site-directed irreversible inhibitors, and both of them have been observed by x-ray crystallography to be covalently bound though Schiff base linkage to PBGS from E. coli and yeast, respectively (3,9); E. coli and yeast PBGSs are mechanistically similar to human PBGS in that they require an active site catalytic zinc ion that is important to the binding and reactivity of the K m -determining substrate molecule (2, 12). 4,7-DOSA has been reported as a very potent irreversible inhibitor for human PBGS (3).…”
Section: Dynamic Interconversion Of Wtϩf12l Hetero-oligomeric Pbgs Qumentioning
confidence: 99%
See 1 more Smart Citation
“…4A, the dose-response curve for succinylacetone inhibition of TgPBGS is comparable with that of HsPBGS, with IC 50 values of ϳ1 M. This is to be expected because the inhibitor binds covalently to a conserved active site lysine, causing suicide inhibition (39). In contrast, the active site-directed, species-specific irreversible inhibitor 4,7-dioxosebacic acid, which is most effective against Zn 2ϩ -requiring PBGS (28,37,40), shows ϳ40-fold selectivity for HsPBGS relative to TgPBGS (Fig. 4B).…”
Section: Inhibition Of Tgpbgs and Heme Biosynthesis In T Gondii-mentioning
confidence: 99%
“…1A). Despite the fact that much is known about the PBGS structure, the sequence of bond-making and bond-breaking events that follow formation of the ternary complex of PBGS with the two substrate molecules is the subject of active discussion (2)(3)(4)(5). Based on an extensive phylogenetic variation in the number and kinds of metal ions used for catalytic and/or allosteric roles, it is possible that the order of chemical events in the enzymecatalyzed reaction mechanism may not be phylogenetically conserved.…”
mentioning
confidence: 99%